Behavioural economics: The missing ingredient that makes sexual health services responsive and acceptable to young South Africans - Smith, Philip John (Department of Medicine, 2022)
Introduction: South African adolescents and young adults (AYA) remain at high risk of HIV infection despite reductions in HIV incidence in older adult populations. This is, in part, attributable to suboptimal levels of health-seeking behaviour. Behavioural economics provides insight into why conventional efforts to generate health-seeking behaviour have struggled to curb HIV infection in South African AYA and in designing more desirable, scalable interventions to better serve youth and promote sexual health. Methods: Focus group discussions gathered information on sexual health service wants from AYA in high HIV disease burden, limited resource communities. Based on this data, three AYA friendly services were designed, including a diagnostic screen (HIV self-testing, HIVST), a prevention intervention (male medical circumcision), and a service platform (mobile clinic). All three studies evaluated acceptability. The circumcision and the mobile clinic studies described service uptake. The mobile clinic study compared uptake of services with four conventional clinics in the same community. Results: Participants recommended that services be easily accessible, friendly services, age appropriate, tailored information, and improved relationships with healthcare workers. Participants in the mobile clinic study (n=304) rated mobile services' acceptability highly (median = 4,6 out of 5), attracting more males proportionally than conventional clinics. The HIVST study (n=224) found high fidelity (96%), usability (median 3.9 out of 5), and acceptability ratings (median 4.3 out of 5). The circumcision study conducted in culturally distinct locations (Cape Town n=50; Soweto n=50) identified that Soweto males in this age range (14-17 years) were 19 times more likely (n=13) to have been circumcised than those in Cape Town (n=1) (HR 18.9, 95% CI 2.37-150.71, p= 0.006) over study duration. Conclusions: Given the high ratings for acceptability, AYA tailored services should be investigated as part of a multipronged approach to diagnostic, prevention, and health system options. Besides development and age considerations, the contrast between MMC uptake in Cape Town versus Soweto indicate that cultural beliefs and tradition may also strongly influence specific key interventions. Overall, using a behavioural economics framework to design and implement AYA recommendations received a positive reception. These findings support recommendations to provide differentiated care to AYA.